Analisis Persepsi dan Perilaku Mahasiswa dalam Pembelajaran Daring di Universitas Nurul Hasanah Kutacane - Yusnaini; Halimatussakdiyah Lubis; Afdhal (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The coronavirus crisis can not only be characterized as a disturbing period of instability, uncertainty, and danger but can also be considered a period of accelerating the diffusion of digital technologies. Colleges around the world have shifted from classroom-based to online-based learning to comply with social distancing recommendations in preventing the wide spread of this pandemic. Online learning can be applied flexibly and provides opportunities to develop wider learning. This study aims to analyze the perceptions and behavior of students in online learning at the Undergraduate Nursing Study Program Students of Universitas Nurul Hasanah Kutacane. This research is a descriptive-analytic correlational study with a cross-sectional study approach. The population is all level II and III students of the undergraduate nursing study program at Universitas Nurul Hasanah Kutacane, totaling 53 respondents. The results of the study generally show that there is a relationship between perception and student behavior in online learning with a p-value of 0.000. Based on the results of this study, it is hoped that the Universitas Nurul Hasanah Kutacane College can support students in online learning through online learning system training, procurement of adequate digital facilities, and benchmarking to other universities.